2003
DOI: 10.1002/app.12429
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the scale factor of a ductile fracture of polymer blends and composites on the basis of the specific interphase concept

Abstract: ABSTRACT:The concept of interfacial layers surrounding inclusions in a host polymer is accepted as a basic source of the scale factor in the simulation of the large-strain deformation and fracture of polymer blends and composites. The essence of the phenomenon is the ductile-brittle transition if the polymer ligament thickness exceeds a critical value, which is determined by the nature of the polymer. Original texture-sensitive constitutive equations have been applied for the simulation of the polymer large-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Particle characteristics such as particle size, shape, as well as surface area and adhesion, will influence mechanical properties such as Young's modulus as well as ultimate mechanical properties, such as elongation at break [1,25,34,35]. PCCs and CPMCs show different behavior and the effect of all these factors can be used to illustrate the difference between these materials.…”
Section: Particle Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Particle characteristics such as particle size, shape, as well as surface area and adhesion, will influence mechanical properties such as Young's modulus as well as ultimate mechanical properties, such as elongation at break [1,25,34,35]. PCCs and CPMCs show different behavior and the effect of all these factors can be used to illustrate the difference between these materials.…”
Section: Particle Characteristicsmentioning
confidence: 99%
“…Oshmyan et al [1] have shown that particle size may lead to changes in failure mode for particulate composites. In their work they simulated two transition points, as illustrated in Figure 4.…”
Section: Particle Sizementioning
confidence: 99%